Quantitative Proteomic Analysis of Human Airway Cilia Identifies Previously Uncharacterized Proteins of High Abundance - Blackburn, Kevin (J Proteome Res, 2017)
Cilia are essential to many diverse cellular processes. Although many major axonemal components have been identified and studied, how they interact to form a functional axoneme is not completely understood. To further our understanding of the protein composition of human airway cilia, we performed a semi-quantitative analysis of ciliary axonemes using label-free LC/MS(E) which identified over 400 proteins with high confidence. Tubulins were the most abundant proteins identified, with evidence for 20 different isoforms obtained. Twelve different isoforms of axonemal dynein heavy chain were also identified. Absolute quantification of the non-tubulin components demonstrated a greater than 75-fold range of protein abundance (RSPH9;1850 fmol vs CCDC103;24 fmol), adding another level of complexity to axonemal structure. Of the identified proteins, approximately 70% are known axonemal proteins. In addition, many previously uncharacterized proteins were identified. Unexpectedly, several of these, including ERICH3, C1orf87, and CCDC181, were present at high relative abundance in the cilia. RT-PCR analysis and immunoblotting confirmed cilia specific expression for eight uncharacterized proteins, and fluorescent microscopy demonstrated unique axonemal localizations. These studies have provided the first quantitative analysis of the ciliary proteome and have identified and characterized several previously unknown proteins as major constituents of human airway cilia.